An RCT META analysis based on the efficacy of Tai Chi exercise therapy on blood pressure and blood lipids in patients with essential hypertension - Xu, Jianan; Huang, Yuerong; Li, Lujia; Zhang, Jianwei; Li, Cuihan; Liu, Mingyu; Ma, Yuxin; Du, Junming; Lyu, Shaojun (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTai Chi is a form of physical and mental exercise. Hypertension, characterized by persistently elevated blood pressure, is a prevalent cardiovascular condition. At present, the effect of Tai Chi exercise cycle on improving the prognosis of patients with essential hypertension, as well as its impact on patients at different stages of hypertension, has not yet been demonstrated. Through meta-analysis, this study systematically evaluated the effects of Tai Chi on hypertensive patients, as well as the roles played by different practice duration, so as to provide evidence-based guidance for future clinical application.MethodsThis meta-analysis, registered in the International Prospective Register of Systematic Reviews (PROSPERO) (CRD42024538168), reviewed RCTs involving Tai Chi interventions for hypertension. Studies were sourced from PubMed, the Cochrane Library, CBM, CNKI, WANFANG, and Embase. Mean differences (MD) and 95% confidence intervals (CI) were calculated using a random-effects model. The sources of heterogeneity were explored using the elimination method one by one and subgroup analysis, supplemented by sensitivity analysis and publication bias assessment.ResultsSeventeen studies were included in the analysis. No adverse events were reported in all the included studies. Tai Chi significantly reduced Systolic Blood Pressure (SBP) (WMD = −9.12; 95% CI = −12.35 to −5.90), Diastolic Blood Pressure (DBP) (WMD = −5.43; 95% CI = −7.22 to −3.64), Total Cholesterol (TC) (WMD = −0.37; 95% CI = −0.62 to −0.12), Triglycerides (TG) (WMD = −0.53; 95% CI = −0.89 to −0.16), and Low-Density Lipoprotein (LDL) levels (WMD = −0.70; 95% CI = −1.12 to −0.28) compared to control groups. Waist circumference (WC) also improved. Subgroup analyses showed that short-term Tai Chi (3 months) was most effective for improving essential hypertension, with a greater impact in grade I hypertension patients compared to those with grade II. No obvious publication bias was found through funnel plots and Egger's test.ConclusionThe results demonstrated that Tai Chi effectively reduced SBP, DBP, TC, TG, and LDL levels, with the most significant improvements observed at 12 weeks. These findings support the use of Tai Chi as a scientifically validated exercise rehabilitation tool in clinical settings and suggest avenues for further research.Systematic Review Registrationidentifier, PROSPERO [CRD42024538168].